2008
DOI: 10.1111/j.1574-6968.2008.01249.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of proteases in the differentiation ofAcanthamoeba castellanii

Abstract: Proteases are significant determinants of protozoan pathogenicity and cytolysis of host cells. However, there is now growing evidence of their involvement in cellular differentiation. Acanthamoeba castellanii of the T4 genotype elaborates a number of proteases, which are inhibited by the serine protease inhibitor phenylmethylsulphonyl fluoride. Using this and other selective protease inhibitors, in tandem with siRNA primers, specific to the catalytic site of Acanthamoeba serine proteases, we demonstrate that s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 31 publications
4
51
0
1
Order By: Relevance
“…This observation supports our previous molecular data regarding the status of both extracellular serine protease and glycogen phosphorylase genes at this stage. Interestingly, Acanthamoeba cells were not able to start encystation, which is in accordance with the previous report of a major role of serine proteases in the encystment and excystment processes in Acanthamoeba (4).…”
Section: Vol 54 2010supporting
confidence: 80%
See 2 more Smart Citations
“…This observation supports our previous molecular data regarding the status of both extracellular serine protease and glycogen phosphorylase genes at this stage. Interestingly, Acanthamoeba cells were not able to start encystation, which is in accordance with the previous report of a major role of serine proteases in the encystment and excystment processes in Acanthamoeba (4).…”
Section: Vol 54 2010supporting
confidence: 80%
“…In previous studies, extracellular serine proteases were silenced using siRNAs, resulting in the Acanthamoeba organisms not being able to degrade human corneal cells (9). More recently, it was established by using siRNAs that serine proteases also play an important role in trophozoite differentiation and reemergence during excystment (4). Furthermore, the role of glycogen phosphorylase in the formation of mature cysts in Acanthamoeba was also established recently by using siRNA (10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown the direct role of extracellular proteases in Acanthamoeba keratitis by co-incubating corneal epithelial cells with Acanthamoeba conditioned medium, which resulted in host cell cytotoxicity [65]. This cytotoxic effect was abolished in the presence of a serine protease inhibitor, phenylmethylsulfonyl fluoride (PMSF), suggesting a crucial role played by serine proteases in the pathogenicity of Acanthamoeba keratitis [38]. Furthermore, pathogenic Acanthamoeba exhibit higher protease activity compared to non-pathogenic amoebae [91].…”
Section: Stromal Invasionmentioning
confidence: 99%
“…These proteases are significant determinants of protozoan pathogenicity and host cell invasion. It has been proposed that proteases play a central role in various processes, such as host cell invasion and way out, cyto-adherence, morphological differentiation, digestion of host proteins, stimulation immune response, and escape from host immune responses [12][13][14][15][16]. However, in spite of their ubiquitous existence in the environment and expression of a lot of proteases capable of eliciting allergic airway inflammation, no report exploring this connection has been published to date.…”
mentioning
confidence: 99%